In Situ Mitochondrial Ca2+ Buffering Differences of Intact Neurons and Astrocytes from Cortex and Striatum - Jorge M A Oliveira (2009)
The striatum is particularly vulnerable to neurological disorders, such as Huntington disease. Previous studies, with nonsynaptic mitochondria isolated from cortical and striatal homogenates, suggest that striatal mitochondria are highly vulnerable to Ca2+ loads, possibly influencing striatal vulnerability. However, whether and how neuronal and glial mitochondria from cortex and striatum differ in Ca2+ vulnerability remains unknown. We test this hypothesis using a novel strategy allowing comparisons of mitochondrial Ca2+ buffering capacity in cortical and striatal neuron-astrocyte co-cultures. We provide original evidence that mitochondria not only in neurons but also in astrocytes from striatal origin exhibit a decreased Ca2+ buffering capacity when compared with cortical counterparts. The decreased mitochondrial Ca2+ buffering capacity in striatal versus cortical astrocytes does not stem from variation in mitochondrial concentration or in the rate of intracellular Ca2+ elevation, being mechanistically linked to an increased propensity to undergo cyclosporin A (CsA)-sensitive permeability transition. Indeed, 1 mu M CsA selectively increased the mitochondrial Ca2+ buffering capacity of striatal astrocytes, without modifying that of neurons or cortical astrocytes. Neither thapsigargin nor FK506 modified mitochondrial Ca2+ buffering differences between cell types, excluding a predominant contribution of endoplasmic reticulum or calcineurin. These results provide additional insight into the mechanisms of striatal vulnerability, showing that the increased Ca2+ vulnerability of striatal versus cortical mitochondria resides in both intact neurons and astrocytes, thus positioning the striatum at greater risk for disturbed neuron-astrocyte interactions. Also, the selective effect of CsA over striatal astrocytes suggests that in vivo neuronal sheltering with this compound may indirectly result from astrocytic protection.